Concentration of the Economic Activity: Comparing Methodologies and Geographic Units - Jenifer Ruiz-Valenzuela; Rosina Moreno-Serrano; Esther Vaya-Valcarce (European Regional Science Association (ERSA), 2006)
Despite the important role of the service sector in the economic activity, the majority of the studies, both at international and at the Spanish level, have focused their attention in determining the degree of concentration of the manufacture sector. The main purpose in this article is to analyze the concentration and the location pattern both of the manufacturing and the service sectors in Catalonia using different methodologies proposed in the economic literature, such as the Ellison&Glaeser index (1997) or the methodology used by O'Donoghue and Gleave (2004), among others. The calculation of the different indices using the municipalities of Catalonia as the geographic unit of the analysis allows us to make a comparison of the results between indices, and also to compare the location pattern and the degree of concentration of the manufacturing and service sectors. Moreover, the results that we obtain for Catalonia are compared with those obtained for other economies (United States, United Kingdom, France, Sweden, etc.). In a second step, we re-calculate these indices using as the geographic unit the local labour systems of Catalonia instead of the municipalities. The election of these two kind of geographic units is motivated thanks to the ongoing debate about what is the ideal geographic unit when analyzing the concentration of economic activity (Duranton and Overman (2006, forthcoming) and Marcon and Puech (2003), at the international level and Viladecans (2004), at the Spanish level). Using local labour systems will overcome the problem of working with geographic units based on administrative borders, like municipalities, that are not based in real economic areas. The calculation of these indices for the two kind of geographic units allows us to compare the results for the two areas. Once we have calculated these indices, we use the techniques of the Exploratory Spatial Data Analysis in order to study the geographic distribution of the concentration of the economic activity. Finally, in order to perform a more in-depth analysis of the relationships among different sectors, we use the Porter (2003) methodology to define clusters of activity.
Keywords: 330